Deskripsi Proses Kognitif Siswa SMP dalam Menyelesaikan Masalah Matematika Berdasarkan Modes Of Representation Teori Bruner - Anisa Rizki Amalia; Tri Nova Hasti Yunianta (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2019)
There are three steps of cognitive processes, that is: 1) acquire new information, 2) transform information; and 3) test the relevance and accuracy of knowledge or evaluation. This study aims to describe the students the cognitive process of junior high school to solve mathematical problems based on Bruner's three modes of representation. The research is qualitative descriptive. The subjects were three students of junior high school; each of them is with high, medium, and low abilities. The results showed that the cognitive processes of high and medium abilities were able to acquire information and transform it to solve the problems in the enactive, iconic, and symbolic representation. For the testing relevance and accuracy, high-ability subject only works in the enactive representation. Middle-ability does in the enactive and symbolic representation. The low-ability subject was able to do all three cognitive processes on questions the enactive representation, but other questions in the iconic and symbolic representation cannot be solved.